On‐pump Cardiac Surgery Enhances Platelet Renewal and Impairs Aspirin Pharmacodynamics: Effects of Improved Dosing Regimens. Issue 5 (29th July 2017) - Cavalca, V; Rocca, B; Veglia, F; Petrucci, G; Porro, B; Myasoedova, V; De Cristofaro, R; Turnu, L; Bonomi, A; Songia, P; Cavallotti, L; Zanobini, M; et al.
Abstract : On‐pump cardiac surgery may trigger inflammation and accelerate platelet cyclooxygenase‐1 renewal, thereby modifying low‐dose aspirin pharmacodynamics. Thirty‐seven patients on standard aspirin 100 mg once‐daily were studied before surgery and randomized within 36 hours postsurgery to 100 mg once‐daily, 100 mg twice‐daily, or 200 mg once‐daily for 90 days. On day 7 postsurgery, immature and mature platelets, platelet mass, thrombopoietin, glycocalicin, leukocytes, C‐reactive protein, and interleukin‐6 significantly increased. Interleukin‐6 significantly correlated with immature platelets. At day 7, patients randomized to 100 mg once‐daily showed a significant increase in serum thromboxane (TX)B2 within the 24‐hour dosing interval and urinary TXA2 metabolite (TXM) excretion. Aspirin 100 mg twice‐daily lowered serum TXB2 and prevented postsurgery TXM increase ( P < 0.01), without affecting prostacyclin metabolite excretion. After cardiac surgery, shortening the dosing interval, but not doubling the once‐daily dose, rescues the impaired antiplatelet effect of low‐dose aspirin and prevents platelet activation associated with acute inflammation and enhanced platelet turnover.